An Intervention to Improve Academic Literacies in a First Year University Biology Course - Kelly-Laubscher, Roisin; Van Der Merwe, Mathilde (Critical Studies in Teaching and Learning, 2023)
In South Africa there are many students, especially those from previously underrepresented groups at university, who successfully gain access to university but do not succeed in completing their degree either within the prescribed time or at all.  One of the barriers to student success at university is the difficulty these students have in accessing the literacy practices of the disciplines.  Therefore, within a first year biology course at a South African University, an intervention that focused on the academic literacy practices in biology was introduced. The intervention was designed around the assignment of writing a lab report. This paper describes this intervention and how it impacted on one student's journey from learning science at school to learning science at university.  A literacy history interview and 'talk around text' interviews were used to assess the student's experience of the intervention. Comparison of the student's first and final drafts of the report revealed changes in the style and format of his writing. These changes in his report writing as well as in his attitude and motivation for writing the report were facilitated by a better understanding of the expectations of writing in university biology. This understanding was mediated largely through the modelling and deconstruction of the expected genre. This highlights not only the importance of providing first year students with examples of the genres they are expected to be writing but also the facilitation of their engagement with these new genres. Without these kinds of intervention many students are unlikely to gain access to disciplinary ways of learning and writing, which ultimately may lead to their exclusion from university.